Mapping and Tagging of Simply Inherited traits - Soriano, J. M.; Badenes, María L. (CRC press, 2017)
The genus Prunus comprises more domesticated species of temperate fruits than any other genera of the Rosaceaes family. The identification of traits of interest, determination of their inheritance and establishing efficient methods of selection are the keys for progress in Prunus breeding. Selection assisted by molecular markers (MAS) is possible if previous identifi cation of molecular markers tightly linked to the target trait is carried out. In this chapter, single inheritance traits identified in Prunus species and results from two methods for searching trait-linked markers: bulked segregant analysis (BSA) and mapping by association analysis between traits of interest and molecular markers are reviewed.